1991
DOI: 10.1128/aem.57.4.1189-1193.1991
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of organotin inhibition of methanogenic bacteria

Abstract: Seven organotin compounds and tin chloride were tested for their effects on the methanogenic bacteria Methanococcus thermolithotrophicus, Methanococcus deltae ALH, and Methanosarcina barkeri 227. The methanogens were strongly inhibited by triethyltin, tripropyltin, and monophenyltin compounds, generally at concentrations below 0.05 mM. Less inhibition by tributyltin and diphenyltin was observed at levels below 0.1 mM, but complete inhibition was observed at a 1 mM concentration. Tin chloride inhibited all meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The observed correlations differ from those reported earlier by Laughin et al and Eng et al In addition, the study indicated that the relationship observed with aerobic systems might not be valid for anaerobic systems. Boopathy and Daniels also observed a similar trend in their study involving methanogenic bacteria and a series of organotin sulfates and chlorides, agreeing with the findings of Belay et al Lascourrèges et al reported a similar observation in their study involving the toxicity of a series of organotins and three pure strains of sulfate‐reducing bacteria.…”
Section: Biological Studiessupporting
confidence: 84%
“…The observed correlations differ from those reported earlier by Laughin et al and Eng et al In addition, the study indicated that the relationship observed with aerobic systems might not be valid for anaerobic systems. Boopathy and Daniels also observed a similar trend in their study involving methanogenic bacteria and a series of organotin sulfates and chlorides, agreeing with the findings of Belay et al Lascourrèges et al reported a similar observation in their study involving the toxicity of a series of organotins and three pure strains of sulfate‐reducing bacteria.…”
Section: Biological Studiessupporting
confidence: 84%
“…Bacillus, Alcaligenes, Alteromonas, Vibrio and Pseudomonas, as it is known that these could tolerate only up to 100 µM TBTC. 13,18,34,35 GC analysis of culture broth, shown in Fig. 2, represents data of TBTC concentration in culture broth extracted after different periods of time.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, to quantify Pb(II) toxicity, we have calculated the exponential phase specific growth rates in liquid medium for the different Pb(II) concentrations studied in addition to MIC and lag times. Lead toxic effects below the lethal concentration were recorded by determining the total cell growth in liquid cultures [48,49]. In this study, cell growth was measured in terms of total cell protein concentration since monitoring culture turbidity by measurement of the absorbance was not feasible in the presence of black precipitates of lead sulfide.…”
Section: Selection Of a Toxicological Indexmentioning
confidence: 99%
“…In this study, cell growth was measured in terms of total cell protein concentration since monitoring culture turbidity by measurement of the absorbance was not feasible in the presence of black precipitates of lead sulfide. In some reports [32,43,49], authors have used a mean inhibitory concentration (IC50) index corresponding to the concentration of pollutants resulting in a decrease of half the total cell growth compared to that of control cultures grown in the absence of pollutants. However, in the present study, in the presence of Pb(II), cultures either did not grow at all or grew after a long lag time and attained final cell yield equivalent to that of Pb-free cultures.…”
Section: Selection Of a Toxicological Indexmentioning
confidence: 99%